The Use of The Educational Game Educandy in Learning English for Young Learners - Riska Magdalena Simanungkalit; Rachel Juliana Manullang; Siti Nur Fadillah; Aldia Rachman Pangestu; Susilawati S (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2023)
Since vocabulary takes an indispensable hold of English language learning, young learners are demanded to build up a broad collection of words. In line with this notion, the current research intended to analyze the effect of Educandy on young learners' vocabulary mastery and their opinions towards its implementation. The writer applied the quantitative and qualitative approach within an embedded mixed-method design. Twenty-four third-grade students School were involved as the participants. The vocabulary test, observation checklist, and questionnaire sheet were encompassed as the data collection instruments. The results of the study revealed that Educandy had a significant effect on young learners' vocabulary retention with a moderate level of effectiveness. Besides, the students also responded positively towards the implementation of Educandy, in which their activeness, motivation, interest, and enthusiasm to learn vocabulary were increased. In conclusion, Educandy clearly has the potential to lead the way toward better learning outcomes for young learners, particularly in vocabulary mastery.